Evolution of density‐dependent movement during experimental range expansions. (23rd October 2017) - Fronhofer, E. A.; Gut, S.; Altermatt, F.
Abstract: Range expansions and biological invasions are prime examples of transient processes that are likely impacted by rapid evolutionary changes. As a spatial process, range expansions are driven by dispersal and movement behaviour. Although it is widely accepted that dispersal and movement may be context‐dependent, for instance density‐dependent, and best represented by reaction norms, the evolution of density‐dependent movement during range expansions has received little experimental attention. We therefore tested current theory predicting the evolution of increased movement at low densities at range margins using highly replicated and controlled range expansion experiments across multiple genotypes of the protist model system Tetrahymena thermophila . Although rare, we found evolutionary changes during range expansions even in the absence of initial standing genetic variation. Range expansions led to the evolution of negatively density‐dependent movement at range margins. In addition, we report the evolution of increased intrastrain competitive ability and concurrently decreased population growth rates in range cores. Our findings highlight the importance of understanding movement and dispersal as evolving reaction norms and plastic life‐history traits of central relevance for range expansions, biological invasions and the dynamics of spatially structured systems in general.